Why stock markets crash : critical events in complex financial systems - Sornette, Didier (Princeton, N.J. : Princeton University Press, 2003)
The book addresses current and enduring concern for all investors, the seemingly mysterious twists and turns the market take .
Includes bibliographical references (p. 397-418) and index.
opc 28/10/16
Loans
Keywords: Financial crises; Stocks; Stock exchanges; Financial crises; Critical phenomena (Physics); Complexity (Philosophy)